Why valence is not enough in the study of emotions: behavioural differences between regret and disappointment - Martinez, Luis Fructuoso (2008)
This paper reflects on the role of emotions on decision-making. The authors stress the limitations of a valence (“positivity” versus “negativity”) based approach. Emotions and their experiential content are synthetically exposed. Research has shown that ever closely related emotions – such as regret and disappointment -, whether anticipated or experienced, have differential influences on the behavior on decision makers. This favours emotion-specific research in decision-making context, i.e., the pragmatic “feeling-is-for-doing” approach. We believe the emotional system is the primary motivational system for goal-directed behavior. DOI: http://dx.doi.org/10.17575/rpsicol.v22i2.349